Analysis Of The Effect Of Hemodialysis Frequency On Hemoglobin, Ureum, Creatinine And Albumin Levels In Chronic Kidney Failure Patients At Praya Hospital - Yunan Jiwintarum; Kurnia Anindita; Erlin Yustin Tatontos; Yudha Anggit Jiwantoro (Poltekkes Kemenkes Mataram, 2026)
Chronic Kidney Disiase (CKD) is a progressive loss of kidney function characterized by the inability of the kidneys to excrete waste and maintain metabolic balance. When kidney function declines, erythropoietin production decreases, resulting in anemia. other complication, such a hypoalbuminemia, are also common. Urea and creatinine levels are vital parameters of assessing kidney function. Hemodialysis is a common therapy for CKD patients; therefore, evaluating laboratory parameters such as haemoglobin, urea, creatinine, and albumin levels according to the frequency of hemodialysis is essential to determine treatment effectiveness. This analytical observational study with a cross-sectional design evaluated the effectiveness of bi-weekly hemodialysis among 32 chronic kidney disease patients at Praya General Hospital in May 2025. The results indicated that while routine hemodialysis significantly reduced urea levels from 137.9 mg/dL to 17.6 mg/dL and creatinine from 10.7 mg/dL to 2.5 mg/dL, these metabolic waste parameters tended to increase slightly after six months. In contrast, hemoglobin levels remained relatively stagnant at approximately 8.2–8.3 g/dL, signifying persistent moderate anemia despite regular treatment. Notably, albumin levels showed a steady and gradual improvement over the six-month period, rising from 3.4 g/dL to 4.0 g/dL, which suggests an enhanced protein status in patients adhering to the prescribed hemodialysis frequency.